Struktur Kepemilikan, Komisaris Independen, Ukuran Perusahaan, dan Financial Distress Pada Perusahaan Manufaktur di Indonesia - Nimas Kurniawati; Frank Aligarh (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2021)
The objective of this study is to examine empirically the influence of institusional ownership, manajerial ownership, the proportion of independent commissioners, the amount of the board of directors, firm size, liquidity, and leverage on the financial distress. this research analyzed manufacturing companies listed on the Indonesia Stock Exchange for the periode 2017-2019. The data used secondary data from the company’s annual financial statements. The population in this study is all of the manufacturing companies listed on the Indonesia Stock Exchange. The research sample used purposive sampling technique. The final sample was obtained as many as 41 companies. The analysis technique used is logistic regression The result of the study reveals that Institusional ownership, the amount of the board of directors, liquidity, has a negative effect on financial distress, and leverage has a positive effect on financial distress. mean while, manajerial ownership, the proportion of independent commissioners, firm size did not effect on financial distress